ANALISIS KONTEN PADA AKUN TIKTOK @STORY’ISLAM PERSPEKTIF DAKWAH - Rozi; Refika Mastanora (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
This research aims to analyze the da'wah content on the TikTok @story'Islam account and analyze the effect on the audience. Using the content analysis method, this research examines the da'wah material presented and the effects on the da'wah material during the last three months. The research results show that the TikTok account @story'Islam presents three main categories in its preaching material, namely aqidah, sharia, and morals. These materials are packaged in attractive short video formats, use language that is easy to understand, and utilize social media trends to attract users' attention. Apart from that, this research also found that the effects of the da'wah content presented can be categorized into three aspects, namely cognitive, affective and behavioral effects. From a cognitive perspective, the audience experiences an increase in Islamic insight; affectively, some content evokes religious emotions, such as encouragement to repent; and behaviorally, there are changes in daily Islamic practices, such as increasing worship. Thus, this research confirms that social media platforms such as TikTok can be an effective means of spreading Islamic values, as long as the content is designed strategically and in accordance with the principles of da'wah.